Queer images : a history of gay and lesbian film in America - Benshoff, Harry M., 1963- (Genre and beyond., 2006)
'Queer Images' chronicles the representation of lesbian, gay, bisexual and queer sexualities over 100 years in American film. This book explores not only the ever-changing images of queer characters onscreen, but also the work of queer filmmakers and thecultural histories of queer audiences.